2021
DOI: 10.3390/land10111130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urbanization and Industrial Structure on Carbon Emissions: Evidence from Huaihe River Eco-Economic Zone

Abstract: Rapid urbanization in China greatly contributes to carbon emissions, while the industrial structure greatly contributes to changes in the variation of carbon emissions. This research addresses the impact of urbanization and industrial structure on carbon emissions from 2010 to 2018, by focusing on the Huaihe River Eco-economic Zone, which is an important economic corridor along the north–south division of China. Although many studies have focused on investigating the impact of urbanization or industrial struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…When considering this body of work, we note that whilst identifying the driving mechanisms and factors behind carbon emissions is key to formulating emission reduction policies and implementing scenario simulations, no uniform conclusions have yet been reached. This is not to say that studies have not addressed the relationship between different drivers and carbon emissions-for example, we note that Solarin et al [27] found a stable long-term equilibrium relationship between the level of urbanization and carbon emissions, and previous research has shown that the driving factors of carbon emissions include population structure [28], GDP [29], industrialization [30], energy consumption [31], urbanization level [32], and land-use change [33]. The study methods employed include least order squares [34], the STIRPAT model [35], the LMDI model [36], vector autoregressive models [37], geographically weighted regression models [38], and multiplier effects [39].…”
Section: Background Of the Studymentioning
confidence: 80%
“…When considering this body of work, we note that whilst identifying the driving mechanisms and factors behind carbon emissions is key to formulating emission reduction policies and implementing scenario simulations, no uniform conclusions have yet been reached. This is not to say that studies have not addressed the relationship between different drivers and carbon emissions-for example, we note that Solarin et al [27] found a stable long-term equilibrium relationship between the level of urbanization and carbon emissions, and previous research has shown that the driving factors of carbon emissions include population structure [28], GDP [29], industrialization [30], energy consumption [31], urbanization level [32], and land-use change [33]. The study methods employed include least order squares [34], the STIRPAT model [35], the LMDI model [36], vector autoregressive models [37], geographically weighted regression models [38], and multiplier effects [39].…”
Section: Background Of the Studymentioning
confidence: 80%
“…International experience shows [18,19] that in the primary stage of urban expansion, the industrial structure of a country or region is dominated by the primary industry, and the demand for energy use is not significant, which has no significant impact on carbon emissions. In the development stage of urban expansion, the proportion of primary industry continues to decline, the secondary industry becomes the dominant industry, and the demand for energy increases dramatically, leading to a rapid increase in carbon emissions.…”
Section: International (Regional) Patterns Of Urban Expansion and Car...mentioning
confidence: 99%
“…The urbanisation process will inevitably have an impact on increasing the use of energy, resulting in the emission of large amounts of greenhouse gases such as CO 2 (Haouraji et al, 2021;Mata et al, 2021;Pang et al, 2021). Ding et al (2021) analysed the impact of 182 prefecture-level cities in China on carbon emissions during rapid urbanisation.…”
Section: Impact Of Urbanisation On Carbon Emissionsmentioning
confidence: 99%